Sexual Motives in Heterosexual Women With and Without Sexual Difficulties. Issue 2 (17th February 2017) - Watson, Erin; Milhausen, Robin R.; Wood, Jessica; Maitland, Scott
Abstract : Previous research indicates that women with sexual problems may have different reasons for engaging in sex than women who are not experiencing sexual problems. The current study investigated whether reasons for sex differed by women reporting high versus low overall sexual functioning, as assessed by the Female Sexual Function Index (FSFI) (Rosen et al., 2000). As low desire and inability to achieve orgasm are the two most commonly reported sexual problems for women, the study also investigated whether women with and without problems specifically related to sexual desire or orgasm cited different reasons for sex. The sample consisted of 446 heterosexual women between the ages of 18 and 61 who completed an online questionnaire assessing reasons for sex and sexual functioning. Women with low sexual functioning overall were more likely to endorse insecurity reasons for sex, while women with high sexual functioning overall were more likely to endorse physical reasons for sex. Women experiencing low desire specifically were less likely to endorse emotional and physical reasons for sex than women without desire difficulties. Women experiencing orgasm difficulties specifically were more likely to endorse insecurity reasons for sex than women without orgasm difficulties. The variance accounted for was low in all cases. This research offers insights into the important but limited role sexual functioning may play in the broader context of women's sexual motivations.